2019
DOI: 10.1038/s41398-019-0651-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling resilience in adolescence and adversity: a novel framework to inform research and practice

Abstract: Recent conceptualisations of resilience have advanced the notion that it is a dynamic and multifaceted construct. However, its adaptive components, especially those forged by adversity, have not been fully realised, and its neurobiological and psychosocial underpinnings are yet to be meaningfully integrated. In part, this is because a developmental perspective is often neglected in the formulation of resilience. In this review, we consider the findings of resilience research, with a specific emphasis on the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 178 publications
(211 reference statements)
4
89
0
3
Order By: Relevance
“…Coping explains moderate amounts of variance in cross-sectional and prospective depression risk, playing multiple roles in developmental cascades towards mood disorder (Zimmer-Gembeck and Skinner, 2016). Successful coping with adversity can also decrease risk for mood disorder and resilience is a protective factor with adaptive components that are developed primarily in the context of adversity (Malhi et al, 2019b). As highlighted in MDcpg 2015 , the development of resilience is a key target of all treatments for mood disorders.…”
Section: Aetiology and Pathogenesis Of Mood Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Coping explains moderate amounts of variance in cross-sectional and prospective depression risk, playing multiple roles in developmental cascades towards mood disorder (Zimmer-Gembeck and Skinner, 2016). Successful coping with adversity can also decrease risk for mood disorder and resilience is a protective factor with adaptive components that are developed primarily in the context of adversity (Malhi et al, 2019b). As highlighted in MDcpg 2015 , the development of resilience is a key target of all treatments for mood disorders.…”
Section: Aetiology and Pathogenesis Of Mood Disordersmentioning
confidence: 99%
“…Consistent with these more holistic views of mental health, resilience refers to the ability to adapt to, and recover from, stress; not simply the absence of vulnerability (Malhi et al, 2019b). There is evidence that resilience plays a mitigating role across all stages in the management of mood disorders (see MDcpg 2015 , and consideration of coping responses above).…”
Section: A Framework For Treatment: Actions Choices Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience in the management of depression has been formulated as an adaptive process that can defend against depression through strengthening processes such as tempering and fortification. 26 In patients where pharmacotherapy is deemed necessary from the outset, because of patient preference or symptom severity, it is important to ensure that the necessary Actions have been undertaken. This is because it has been shown that the implementation of psychological therapies alongside pharmacotherapy enhances outcomes, and because adverse social and lifestyle factors often maintain depression.…”
Section: Response Remission Recovery Resiliencementioning
confidence: 99%
“…Resilience in the management of depression has been formulated as an adaptive process that can defend against depression through strengthening processes such as tempering and fortification 26 . This presents an opportunity for building resilience, initially through psychological interventions.…”
Section: Management Of Depressionmentioning
confidence: 99%